Ceramic Conductors - Gazda, Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue of Crystals contains papers focusing on various properties of conducting ceramics. Multiple aspects of both the research and application of this group of materials have been addressed. Conducting ceramics are the wide group of mostly oxide materials which play crucial roles in various technical applications, especially in the context of the harvesting and storage of energy. Without ion-conducting oxides, such as yttria-stabilized zirconia, doped ceria devices such as solid oxide fuel cells would not exist, not to mention the wide group of other ion conductors which can be applied in batteries or even electrolyzers, besides fuel cells. The works published in this Special Issue tackle experimental results as well as general theoretical trends in the field of ceramic conductors, or electroceramics, as it is often referred to.